Implementasi Pembelajaran Aqidah Akhlak dalam Membentuk Adab Berbusana Peserta Didik - Multi Meliana; Murniyetti Murniyetti (An-Nuha, 2023)
This research is motivated by the large number of young women who wear clothes that are not in accordance with Islamic teachings. Therefore it is necessary to have guidance from various parties to shape the manners of dressing young women. One of them is learning in madrasas. The purpose of this study was to find out the implementation of Aqidah Akhlak learning in shaping the dress code of students of class XI MAN Lima Puluh Kota. This study used a qualitative research method with research informants: madrasa heads, Aqidah Akhlak teachers, and class XI students. Data collection techniques using observation, interviews, questionnaires and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. The results of this study are: 1) the teacher's Aqidah Akhlak lesson plan prepares learning tools in the form of annual semester programs, syllabus, lesson plans and assessment tools. In preparing learning tools, the teacher considers the appropriate time allocation, models, methods, sources, and learning media for dress etiquette material. 2) the implementation of Aqidah Akhlak learning in forming dress etiquette, the teacher applies the discovery learning model by using a learning method that is a combination of lecture, question and answer, and demonstration methods and is assisted through learning media in the form of PPT and learning resources Aqidah Akhlak package books. Evaluations carried out by Aqidah Akhlak teachers in forming dress etiquette are observations for attitude assessment, tests in the form of descriptions and objectives for knowledge assessment, as well as portfolio assessment for skills assessment.